Depression Predicts Global Functional Outcomes in Individuals at Clinical High Risk for Psychosis. Issue 4 (17th November 2021) - Deng, Wisteria; Addington, Jean; Bearden, Carrie E.; Cadenhead, Kristin S.; Cornblatt, Barbara A.; Mathalon, Daniel H.; McGlashan, Thomas H.; Perkins, Diana O.; Seidman, Larry J.; Tsuang, Ming T.; Woods, Scott W.; Walker, Elaine F.; et al.
Abstract : Objectives: While co‐morbid depression is associated with poor functional outcome among patients with schizophrenia, whether depression similarly predicts poorer outcomes in individuals at clinical high‐risk for psychosis (CHR‐P) is not clear. The present study aimed to examine depressive symptoms in relation to long‐term global functional outcomes in the North American Prodrome Longitudinal Study cohort (NAPLS2). Methods: CHR individuals were evaluated clinically at baseline and at 12‐ and 24‐month follow‐ups for depressive and prodromal symptom severity as well as general functioning. Regression models were built to investigate whether baseline positive and depressive symptom scores predicted longitudinal improvement in global functioning. Results: A total of 406 CHR individuals completed the 12‐month follow‐up assessment and 259 CHR individuals completed the 24‐month assessment. Baseline depressive symptoms in the CHR‐P population were found to predict better global functional outcomes at 2 years. Furthermore, the degree of recovery of depressive symptoms in the first year following baseline completely mediated the association between depressive symptoms at baseline and functional improvement at 2 years. Conclusions: Presence of affective symptoms within the CHR‐P population has different implications for prognosis compared with patients with schizophrenia. The present findings support the view that among those at risk for psychosis, depressive symptoms at baseline predict a more favorable course of functional recovery, and highlight the potential importance of treating co‐occurring depressive symptoms at an early stage of psychosis risk. Highlights: Depression among those at clinical high‐risk for psychosis is indicative of an affective subtype, that is, more likely to recover and experience better long‐term outcomes The degree of recovery of depressive symptoms in the first year following baseline completely mediated the association between depressive symptoms at baseline and functional improvement at 2 years This pattern highlights the potential importance of treating co‐occurring depressive symptoms at an early stage of psychosis risk